Quantifying Carbon Sequestration Service Flow Associated with Human Activities Based on Network Model on the Qinghai-Tibetan Plateau - Wang, Qingbo; Liu, Shiliang; Wang, Fangfang; Liu, Hua; Liu, Yixuan; Yu, Lu; Sun, Jian; Tran, Lam-Son Phan; Dong, Yuhong (Frontiers in Environmental Science, 2022)
The flow of ecosystem services between regions as a result of the mismatch of supply and demand has increasingly become a new research focus. Clarifying the spatial regularity of ecosystem service flow is of great significance for realizing regional sustainable development and improving human well-being. This study applied a network model to map the interregional carbon flow based on the supply and demand of carbon sequestration service, and the driving effect of various driving factors was further analyzed. The results showed that the demand for carbon sequestration service on the Qinghai-Tibet Plateau increased steadily from 2000 to 2019, resulting in an increasingly significant difference between supply and demand with more than 20 million tons. In the carbon sequestration service flow network, the number of defined deficit nodes increased to 22 in 2010, but decreased to 21 in 2019. The interrupted edges continued to increase to 16, and the network density dropped to 0.022. The carbon sequestration service flow network on the northeastern parts of the Qinghai-Tibet Plateau was severely damaged. With the high-quality development of animal husbandry, the impact of grazing intensity on the difference between the supply and demand of carbon sequestration service has been weakened. When urbanization reached a certain level, the driving effects of urbanization and agricultural activities increased significantly. The study provided a reference for the use of network models to analyze ecosystem service flow, and provided a theoretical basis and data support for local ecological management decisions.